Seismic Performance of Damaged Dovetail Joints with Different Damaged Degrees in Timber Frames - Hua Ma; Xinyu Luan; Zhenbao Li; Haijian Cui; Wenjing Wang; Jia Song (Advances in Civil Engineering)
The mortise and tenon joints are the main connection forms used in ancient timber buildings, and damaged joints have a critical effect on the safety of a timber structure. There are three main damaged cases of dovetail joints which are pulling, contraction, and mixing damages. In this study, using a theoretical analysis of the stress distribution in a mortise and tenon joint resulted from the pullout damage, a theoretical equation for the resisting moment of the joint was proposed. A finite element model was used to simulate the cyclic displacement loading of a frame with intact joints and with different levels of pulling and contraction damaged joints. The results show that the moment capacities both for the test and the simulation were in good agreement with each other. The simulation results also indicated that there are no changes in the capacity and energy dissipation of the pulling damaged joint compared to that of the intact joint, and good seismic performance still was provided when the pulling damage was less than 2/5 of the joint length. However, the capacity of the contraction damaged joint was significantly reduced, and its seismic performance was tolerably lost. The seismic performance of a mixing damaged tenon with the same degree of pulling damage was between that of the pulling damaged tenon and the contraction damaged tenon, and generally, it was controlled by the contraction damage. The friction between the tenon and the mortise is the main source of resisting moment and energy dissipation ability.